EFFECT OF WASHING AND STORAGE METHODS ON THE QUALITY OF SEAWEED POWDER Ulva Sp. IN CV. LARS - Arie Hijriyah; Tri Widayati Putri; Jawiana Saokani Sofyan; Zul Khairiyah (Institut Teknologi dan Bisnis Maritim Balik Diwa, 2026)
Ulva sp. is a type of seaweed that has high potential as a sea vegetable with sufficient protein and economic value. This study aims to determine the effect of washing and storage methods on the quality of Ulva sp. powder in CV. Lars. The research was conducted using two washing methods (seawater and fresh water), two types of packaging (black plastic and aluminum foil), and storage time of 0, 15, and 30 days at room temperature. The parameters analyzed included moisture content, impurity content, color (CIELab model), and organoleptic test. The results show that washing with fresh water packaged in aluminum foil gives the best results in keeping moisture content low, maintaining its natural green color, and providing an acceptable taste and aroma. The average impurity level is below 1%, indicating that both washing methods are equally effective. The discoloration towards yellow occurs more often in washing using seawater. In conclusion, the combination of washing with fresh water and storage using aluminum foil packaging is the best treatment in maintaining the quality of Ulva sp powder. during storage